Brand Ambassador, Korean Wave dan Brand Image dalam Pembentukan Brand Awareness Pada Produk Skincare Somethinc di Kota Semarang - Murti, Rizki Adhitya; Pantawis, Setyo (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
Building brand awareness is a marketing strategy that can lead consumers to develop preferences for brands and products. By utilizing Hallyu culture or the Korean Wave to improve the brand image of Somethinc products, it can have a positive influence on brand awareness as much as possible. This research aims to determine the influence of the Ambassador brand, Korean wave and brand image in forming brand awareness of Somethinc skincare products. The research sample used was 97 respondents with the criteria of having used Somehinc products in Semarang City. The sampling method uses a non-probability sampling approach with purposive sampling technique. Multiple regression analysis was used to analyze the data in this study. The research results show that brand ambassadors and brand image have a positive and significant effect on brand awareness. Meanwhile, the Korean Wave has no effect on brand awareness.